2011
DOI: 10.1126/science.1199435
|View full text |Cite
|
Sign up to set email alerts
|

Hibernation in Black Bears: Independence of Metabolic Suppression from Body Temperature

Abstract: Black bears hibernate for 5 to 7 months a year and, during this time, do not eat, drink, urinate, or defecate. We measured metabolic rate and body temperature in hibernating black bears and found that they suppress metabolism to 25% of basal rates while regulating body temperature from 30° to 36°C, in multiday cycles. Heart rates were reduced from 55 to as few as 9 beats per minute, with profound sinus arrhythmia. After returning to normal body temperature and emerging from dens, bears maintained a reduced met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
313
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(331 citation statements)
references
References 21 publications
15
313
2
1
Order By: Relevance
“…Two prominent mechanisms in re-organizing energy balance are (i) the use of internal energy storage from lipids and carbohydrates and (ii) the reduction of energy expenditure via hypometabolism. In endothermic vertebrates in which metabolism is high due in part to thermogenesis, several energy conservation strategies have evolved, such as torpor (metabolic suppression with a daily return to normothermia) or hibernation (profound metabolic suppression and reduced body temperatures over several days) [1][2][3]. These mechanisms reap large benefits, in part, because of the effects of low body temperature (T b ) on metabolic rate.…”
Section: Introductionmentioning
confidence: 99%
“…Two prominent mechanisms in re-organizing energy balance are (i) the use of internal energy storage from lipids and carbohydrates and (ii) the reduction of energy expenditure via hypometabolism. In endothermic vertebrates in which metabolism is high due in part to thermogenesis, several energy conservation strategies have evolved, such as torpor (metabolic suppression with a daily return to normothermia) or hibernation (profound metabolic suppression and reduced body temperatures over several days) [1][2][3]. These mechanisms reap large benefits, in part, because of the effects of low body temperature (T b ) on metabolic rate.…”
Section: Introductionmentioning
confidence: 99%
“…A hibernating brown bear (Ursus arctos) routinely spends 5-7 mo per year in continuous dormancy with no food or water intake, no urination, and no defecation (19,36). During this time, bears appear to be resistant to loss of muscle mass, strength, or bone density (18,24,29,43,14,44). During hibernation bear body temperature is downregulated only slightly, fluctuating from ϳ37°C to a minimum of 30°C, as found in brown and in black bears (Ursus americanus) (17,26,27,36,43), whereas O 2 consumption rate is downregulated by 75% (43).…”
mentioning
confidence: 99%
“…In spite of substantial downregulation of ventilation and heart rate, most hibernators likely experience only slight or no hypoxia and in some ground squirrels arterial O 2 tension (PO 2 ) is normal during torpor (16). As opposed to smaller hibernators that exhibit periods of spontaneous arousals back to normothermic temperature and metabolic rate (33, 31), bears do not arouse to normothermic temperature during winter but have shallow multiday cyclic (1.6 -7.3 days) fluctuations in body temperature (43). Nevertheless, as demonstrated in a recent study (43), bears exhibit a strong active aerobic metabolic depression and a weight-specific metabolic rate similar to that of smaller hibernators (20,25,43), and for this reason, they are now recognized as true hibernators, even though they do not show the dramatic drop in body temperature and arousals typical of small hibernators (43).…”
mentioning
confidence: 99%
“…Information on foraging behavior (Farley and Robbins 1995;Lopez-Alfaro et al 2013;Robbins et al 2012b) and the distinct phases of weight change throughout the year was presented by Nelson et al (1983), Hilderbrand et al (1999), and Schwartz et al (2003). Tøien et al (2011) documented a reduction in metabolism during hibernation to 25 % of basal rates independent of lowered body temperature, suggesting other endogenous factors may be involved in triggering the physiological changes accompanying hibernation. Studies of the processes regulating hibernation revealed a higher proportion of plasma unsaturated fatty acids during winter than during summer months, and increased leptin concentrations directly before hibernation corresponding to maximal fat content (Hissa et al 1998;Tsubota et al 2008).…”
Section: Plin2mentioning
confidence: 99%
“…Only the members of Ursus exhibit a continuous hypometabolic state for the entirety of hibernation (Pagès et al 2008;Tøien et al 2011). The mechanisms underlying these seasonal transitions in brown bears have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%